Urban cinesemiotics: a theory-based critical interpretation of Chicago in the cinema of the 1980s and 2010s - Goharipour, Hamed (Kansas State University, 2020)
In many academic fields today, cinematic representations are rich sources through which researchers recognize and interpret phenomena. Using cinema as the global form of visual texts is both useful and, to some extent, even necessary in the study of urban phenomena. Geography was the first discipline that continuously attempted to conceptualize the notion of the cinematic city. From then until now, Art, film, media studies, and architecture have considered the relationship between city and cinema. In recent years, although scholars with a background in urban disciplines have addressed this interdisciplinary topic, little in the way of effective, continuous utilization of movies in urban studies has occurred. The failure is not necessarily appreciation, but capability; arguably, the lack of an urban-oriented methodology is an important reason why urban studies has not paid deep attention to the cinema to date. From a critical interpretive position, this study has developed a dynamic methodological framework to show how researchers may interpret cities and urban experiences through cinema. Based on Charles S. Peirce’s triadic model of semiotics, using urban theory, ‘urban cinesemiotics’ helps urbanists get closer to the final interpretation of urbanism in cinema. This dissertation employs the two-sided transaction between urban cinesemiotics and urban theory in three distinguished ways. First, the urban theory provides guidelines and attributes that have long fascinated scholars of urban studies by which the interpreter can identify the eligible image-signs from the infinite number of signs in movies. Second, urban theory enables the interpreter to go beyond the immediate and dynamic interpretation of image-signs and reach the final interpretant that provides the discipline with a critical lens to explore and experience cities. Third, urban cinesemiotics provides a context for urbanists to critique long-accepted urban theories and even revise them through the perspective of films. This dissertation interprets the representation of Chicago in the cinema of the 1980s and 2010s. In addition to the 2010s which is contemporary to the time of this writing, this study focuses on the 1980s cinema because during the reign of Mayor Jane Byrne (after 1979) filmmaking was promoted in the city with a vengeance which gave a chance visually to filmmakers to portray a city that was not depicted as much. Many Chicagoan iconic movies were made during the 1980s and represented various and sometimes hidden aspects of the city. In addition to general urban theories by Jane Jacobs and Kevin Lynch, since violence and urban crime have been a popular subject in most of the movies made in the 1980s and 2010s, the theoretical roots of Crime Prevention through Environmental Design constitute the basis for the interpretation of movies. This study shows how Lynch’s five elements (landmark, path, district, edge, node), fundamentals of Jacobs’ theory (neighborhood, diversity, safety, etc.), and the CPTED’s principles (natural surveillance, clear visibility, mixed-use, target hardening, etc.) help us interpret the cinematic representation of Chicago, and how cinema provides a new viewpoint to criticize urban theories and revise them.
Keywords: Urban cinesemiotics; Urban theory; Cinema; Crime; Chicago; City